Characterization of Three Porcine Acinetobacter towneri Strains Co-Harboring tet(X3) and blaOXA-58 - Ma, Jiangang; Wang, Juan; Feng, Jie; Liu, Yingqiu; Yang, Baowei; Li, Ruichao; Bai, Li; He, Tao; Wang, Xinglong; Yang, Zengqi (Frontiers in Cellular and Infection Microbiology, 2020)
Tigecycline is the antibiotic of last resort for the treatment of extensively drug-resistant bacterial infections, mainly those of multidrug-resistant Gram-negative bacteria. The plasmid-mediated tet(X3) gene has recently been described in various pathogens that are resistant to resist tigecycline. We report three tigecycline-resistant Acinetobacter towneri strains isolated from porcine faeces in China, which all contained the tet(X3)-harboring plasmids. A broth microdilution method was used to examine the antimicrobial susceptibility of the isolates, and S1-Nuclease digestion pulsed-field gel electrophoresis (S1-PFGE) was used to characterize their plasmid profiles. The whole-genome sequences of the isolates were determined with the Nanopore PromethION platform. The sequence analysis indicated that the strains were A. towneri. They showed resistance to multiple antibiotics, and all the resistance genes were located on plasmids. The three tet(X3)-harboring plasmids had a similar backbone structure, and all contained blaOXA-58 with various insertion elements (IS). ISCR2 is considered an important factor in tet(X3) mobilization. In addition to ISCR2, we demonstrate that IS26 generates a circular intermediate containing the tet(X3) gene, which could increase the dissemination risk. To our knowledge, this is the first report of tet(X3)- and blaOXA-58-harboring plasmids in A. towneri. Because the IS26 is frequently found in front of tet(X3), research should be directed towards the action of IS26 in the spread of tet(X3).